THE EFFORT OF REUNIFICATION KOREA (A STUDY OF PRESIDENT KIM DAE JUNG GOVERNMENT IN SOUTH KOREA IN 1998-2003 - Fathimatuzzahrah, Dessy (Candi)
Republic of Korea, known as South Korea is a country in East Asian which is located in south of Korea Peninsula. Republic of Korea borders on North Korea in north. Both united until 1948. It borders on Japan Ocean in the east, East Cina Ocean in the south, and Yellow Ocean in the west.In August 22th 1910, Japan occupied Korea based on Aneksasi Agreement. The crisis of the World War II porced Japan looked for the help from founding father of Korea. So that, Japan could occupy the Korea territory more Korea asked Japan to allow it to prepare the independence. The preparation was well done. So, in August 15th 1945 Korea was independent. The liberalism and communism divided Korea in 380 of north latitude. The interferences of both countries divided Korea. In 1950 until 1953, Korea War broken the relationship.Based on the background about the research problems of the study are identified as follows: (1) How politics carrier a President Kim Dae Jung ?; (2) How the background of reunification Korea in 1998 ?; (3) How President Kim Dae Jung?s policy to reunificated Korea in 1998-2003 ?The aims of the research are to identify: (1) Politics carrier a President Kim Dae Jung; (2) The background of reunification Korea in 1998; (3) President Kim Dae Jung?s policy to reunificated Korea in 1998-2003.Key words: reunification, South Korea, Sunshine Policy